O perigo na utilização equivocada dos precedentes. Estudo de caso / The hazard in the Misuse of Judicial Precedents: A case study - Vieira, Artur Diego Amorim (Revista do Programa de Pós-Graduação em Direito, 2015)
This article discusses the dangers of poor training and application of judicial precedents . To do so, will be using the analysis of two concrete cases tried by the High Court of Justice and will be exhibited some considerations regarding the precedent for , in the end, we present the contributions of philosophical hermeneutics as the theme.